Functional dyspepsia in children: A study of pathophysiological factors. Issue 3 (5th August 2020) - Shava, Upender; Srivastava, Anshu; Mathias, Amrita; Kumar, Narvesh; Yachha, Surender Kumar; Gambhir, Sanjay; Poddar, Ujjal
Abstract: Background and Aim: Functional dyspepsia (FD) is common in children, and treatment targeted towards the altered pathophysiology can improve outcome. We evaluated FD children for abnormality of gastric accommodation and emptying, psychological stressors (PS), Helicobacter pylori (HP) infection, and post‐infectious FD. Methods: Diagnosis of FD was based on ROME III criteria. Clinical evaluation including dyspeptic symptom scoring and assessment for PS was performed. Satiety drink test for gastric accommodation, gastroscopy with biopsy for HP infection, and solid meal gastric emptying were performed. Sixty‐seven healthy children were enrolled for assessing PS and satiety drink test. Results: Fifty‐five FD children (33 boys, age 12 [6–18] years) with symptoms for 4 (2–48) months and dyspeptic score of 5 (1–13) were enrolled. PS were more common in FD than in controls (46/55 vs 9/67; P  < 0.001). Median satiety drink volume was 360 mL (180–1320 mL); no patients had satiety drink volume of < 5th centile of healthy children. The frequency (98% vs 85%; P  = 0.01) and severity (65 [10–175] vs 50 [5–130]; P  < 0.001) of postprandial symptoms were higher in FD than in controls. Of the postprandial symptoms, pain (20.3% vs 0%; P  = 0.000) was present only in FD. Delayed gastric emptying was present in 6.5%, HP infection in 11%, and post‐infectious FD in 13% cases. Etiological factor was identified in 87% children, with 20% having multiple factors. Conclusions: Abnormality of gastric sensorimotor function is seen in one‐fourth of FD cases. HP infection and post‐infectious FD are present in 11% and 13% cases, respectively.